SASANA SEWAKA: TINJAUAN SEMANTIK ARSITEKTUR JAWA KRATON KASUNANAN SURAKARTA - Sari, Galuh Puspita (Institute of Research and Community Outreach - Petra Christian University, 2010)
Sasana Sewaka is a pendhapa (an open pavilion) in Kraton (Palace) Kasunanan Surakarta Solo which grew and developed from Javanese architectural values under the influence of European architectural encounters. The meeting of Javanese and European Architectures has a potential to influence the existing architecture. A form of architecture will describe the visual language (composition) through a comprehendible visualization according to its appearance and thus the forming result of architecture can give a meaning that can be communicated.